Fertility Treatment Resulting in Live Births in Women with Asthma – Associated with Perennial Allergy? - Tidemandsen, Casper (J Asthma Allergy, 2020)
BACKGROUND: Asthma has been linked with prolonged time to pregnancy compared to healthy controls, also asthma has been linked to a higher need for fertility treatment. However, knowledge of the possible association between allergy and need for fertility treatment is limited. Our aim was to explore a possible difference in having had fertility treatment in women with asthma and live births in those with perennial allergy (animals, fungi and dust mites) compared to no allergy/seasonal allergy. The primary outcome of interest was fertility treatment. PATIENTS AND METHODS: Women enrolled in the Management of Asthma during Pregnancy (MAP) program at Hvidovre Hospital, DK, were included in the present analysis provided they fulfilled the following criteria: 1) diagnosed with asthma and current anti-asthma therapy and 2) first visit to the respiratory outpatient clinic within the first 18 weeks of pregnancy. Participants were divided into two groups: asthma with perennial allergy (cases) and asthma with seasonal/no allergy (controls). Logistic regression analysis was applied, and findings expressed as odds ratios (OR). RESULTS: Among women with asthma and perennial allergy (n=544 cases), 13.8% (n=75) had fertility treatment, compared to only 10.1% (n=39) among women with asthma and seasonal/no allergy (n=388, controls) (OR 1.43, 95% CI 0.95–2.16, p=0.087). This association remained statistically insignificant after adjusting for confounders, including BMI (OR 1.19, 95% CI 0.77–1.84, p=0.433). In women ≥35 years of age, 28% (n=44) and 20% (n=19), respectively, among cases and controls had fertility treatment (OR 1.60, 95% CI 0.87–2.94, p=0.132), and likewise, statistically insignificant after adjusting for confounders (OR 1.41, 95% CI 0.74–2.69, p<0.293). CONCLUSION: In women with asthma and live births, our study revealed a trend towards an association between perennial allergy and a higher need for fertility treatment compared to seasonal/no allergy.